HnRNP K plays a protective role in TNF-α-induced apoptosis in podocytes. Issue 3 (12th June 2018) - Zhao, Shili; Feng, Junxia; Wang, Qi; Tian, Lu; Zhang, Yunfang; Li, Hongyan
Abstract : Apoptosis of podocytes contributes to proteinuria in many chronic kidney diseases. The cytokine, tumor necrosis factor-α (TNF-α) is thought to be involved in podocyte apoptosis, but the underlying mechanism is not understood. In our study, we established a model of TNF-α-induced apoptosis by isolating primary podocytes from mice. After exposing cells to TNF-α, we determined the expression levels of heterogeneous nuclear ribonucleoprotein K (hnRNP K) and cellular FLICE-inhibitory protein (c-FLIP) and the phosphorylation levels of glycogen synthase kinase β (GSK3β) and extracellular signal-regulated kinase (ERK). We then knocked down or overexpressed the levels of hnRNP K and observed its effects on the expressions of c-FLIP, caspase-8, caspase-3, and the phosphorylation of GSK3β and ERK. In addition, we examined the percentage of cells undergoing apoptosis and studied cell cycle distribution. We found that TNF-α induced apoptosis in podocytes and that the expressions of hnRNP K and c-FLIP were significantly decreased, whereas the phosphorylations of GSK3β and ERK were significantly increased. Both gene knockdown and overexpression of hnRPN K resulted in varied expressions/phosphorylations of c-FLIP, GSK3β, and ERK. Moreover, decreased hnRPN K expression contributed to increased levels of caspase-8 and capase-3, as well as an increase in cell apoptosis and G0/G1 arrest. In conclusion, down-regulated expression of hnRNP K by TNF-α resulted in a decrease in the expression of c-FLIP as well as increases in phosphorylated GSK3β, ERK, caspase-8, and caspase-3, and then critically contributed to the podocyte apoptosis.